A sermon of hearing, or Iewell for the eare VVherein is contained a preparatiue to the hearing of the word, with sundry lessons of instruction for the eare, which who so hath not learned and digested, can neither enter into Gods temple with reuerence, nor depart with profit - Wilkinson, Robert (Early English Books Online / EEBO, 1593)
eebo-0199